Analisis efektivitas pelaksanaan pemungutan retribusi sampah di Kabupaten Rokan Hulu - -, jufaizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
AbstractJufaizal,1225077.2016.Analysis of Effectiveness of levy garbage collection inRokanHulu.AdvisorI:Andi Afrizal,SE.,M.Si,AK,CA, and AdvisorII:Seprini,SE.,MM.This study aims to determine the effectiveness of the implementation of fee collection bins in RokanHulu. Informants in this study is the one who really knows or actors that are directly involved withresearch problems concerning this wasteretribution. The results of this study show that theeffectiveness of 4 (four) years in a row from 2011, 2012, 2013 and 2014 respectively was 68.33%,95.91%, 96.14% and 107.95 %. The effectiveness of the waste levy / hygiene for the period of 2011 to2014reached an average of 92.08% annually mean that local governments need Rokan Hulu fairlystrong effort in optimizing its officers to levy the fees of waste / cleanliness of the houses of citizens /shops and other public facilities. Suggestions put forwardthe local government needs to pay attentionand are committed to achieving the targets that were obtained for the years to come and should alsoconsider the contribution of local taxes and levies from other sectors such as a hotel, restaurant andparkingfacilities for example to further increase revenue (PAD ) in Rokan Hulu.